Suppose 0 = 5*p + 5, -4*z - p = -3*z - 2. Solve -5*a = -z*a for a.

0

Let h(f) = -f**2 + 14*f - 9. Let l be h(13). Suppose 2*t = -l*x - x + 13, x = 3*t + 6. Solve 0 = -x*i + 4*i + 1 for i.

-1

Suppose 0 = -4*p + 3*p + 2. Solve 20 = -p*h - 3*h for h.

-4

Suppose -5*t - 1 = 3*p, 3*p + 12 = 7*p. Let u(w) = 4*w**2 - w. Let l be u(t). Solve 3 = -5*x + l for x.

3

Let p be (4 + 7/(-2))*4. Solve 4*t = 5*t + p for t.

-2

Let d be 624 + (-23)/(-4). Let c = 4 + 0. Let h = c + -1. Solve d*x - 9 = h*x for x.

3

Suppose 0 = -3*a - 6 + 27. Let f(h) = -6*h + 5*h - h3 + 10 + 6*h2 + 8*h. Let y be f(a). Solve -w = w + y for w.

-5

Let c = 50 - 45. Solve 0*f = f - c for f.

5

Suppose 5*p + 5*z - 55 = -0*p, 3*z + 12 = 0. Solve -5*n = -0*n + p for n.

-3

Suppose 2*y + r = 2*r - 1, 3*y + 19 = 5*r. Solve 4 - 10 = -y*q for q.

3